(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Economists expect that CPTPP, together with the EU-Vietnam Free Trade Agreement (FTA), will bring enormous economic benefits to Vietnam, by increasing the price competitiveness of Vietnam’s exports in key markets and boosting foreign direct investment (FDI), promoting economic development and creating millions of jobs, including in small and medium-sized enterprises. More importantly, CPTPP will help facilitate domestic reforms in many areas and build an environment for a competitive economy. The purpose of this article is to clarify the impact of free trade agreements on Vietnamese trade unions, which are considered exclusive in representing workers throughout the territory of Viet Nam but will no longer play this role when Viet Nam joins next-generation trade agreements.